(untitled) («СОВРЕМЕННЫЕ ТЕХНОЛОГИИ КОМПЬЮТЕРНОЙ ЛИНГВИСТИКИ», 2024)
The current excitement over data-driven artificial intelligence makes headlines across the world, including in Africa. Accordingly, AI is supposed to enable an exponential growth in digital resources and level the playing field for less-resourced languages. However, this enthusiasm largely eludes the correlation between AI capacity and the availability of massive and well-curated datasets. In this regard, for the most part, African languages do not fulfill the basic requirements to participate in the new “revolution”. The Songhay language is a case in point, with slow and continuous work done over two decades to develop even a basic tool like a spellchecker. Still, even limited experience with localization and building corpora helps toward developing more advanced tools and content over time.